Enhancing Batik SME`s Competitive Advantage Through Sustainable Performance, Big Data, SCM, e-CRM, and Circular Economy - Nanang Adie Setyawan; Novitasari Eviyanti; Mona Inayah Pratiwi; Hadiahti Utami; Sri Eka Sadriatwati; Destine Fajar Wiedayanti; Bagus Yunianto Wibowo (LP2M IAIN Palopo, 2026)
This study examines how Big Data Analytics Capabilities (BDAC) enhance sustainable performance and competitive advantage among batik MSMEs in Central Java. Grounded in the Resource-Based View (RBV), the research explores the mediating roles of Supply Chain Management Capabilities (SCMC), Electronic Customer Relationship Management (e-CRM), and Circular Economy Practices (CEP). Using a quantitative explanatory approach, survey data were collected from 150 batik MSME owners and managers and analyzed through Structural Equation Modeling (SEM) with AMOS. The findings reveal that BDAC significantly improves SCMC, e-CRM, and CEP, while also directly influencing sustainable performance. SCMC, e-CRM, and CEP partially mediate the relationship between BDAC and sustainable performance. In addition, sustainable performance significantly strengthens competitive advantage. The study confirms that data-driven capabilities alone are insufficient to create long-term competitiveness unless supported by effective supply chain integration, digital customer management, and circular economy implementation. This research contributes to sustainable supply chain and MSME literature by integrating big data analytics, sustainability, and competitive advantage within traditional creative industries. Practically, the findings offer strategic insights for batik MSMEs and policymakers in supporting sustainable digital transformation.